REVOLUTIONING E-COMMERCE: INVESTIGATING THE EFFECTIVENESS OF AI-DRIVEN PERSONALIZATION IN INFLUENCING CONSUMER PURCHASING BEHAVIOR - Ingriana, Alberta; Rolando, Benediktus (LPPM Universitas Dinamika Bangsa, 2025)
The rapid advancement of artificial intelligence (AI) has revolutionized the e-commerce industry by enabling personalized shopping experiences that cater to individual consumer preferences and behaviors. This study employs a systematic literature review methodology, analyzing peer-reviewed articles from the Scopus database published between 2020-2024, to comprehensively examine the impact of AI-driven personalization on consumer behavior in e-commerce. The review methodology followed the PRISMA protocol, ensuring a rigorous and transparent selection process of relevant literature. The findings reveal three key impacts of AI-driven personalization. First, it enhances customer engagement through personalized recommendations, leading to a 15-30% increase in conversion rates. Second, it improves operational efficiency through AI-powered chatbots and automated customer service, reducing response times by up to 80%. Finally, it strengthens brand loyalty through personalized marketing campaigns, resulting in a 20-40% increase in customer retention rates. However, the study also highlights the importance of addressing ethical considerations, particularly data privacy concerns and the need for transparent data practices. The implications suggest that e-commerce businesses should prioritize AI integration while maintaining responsible data management to build consumer trust. The limitations of this research include the focus on a specific time frame and the reliance on a single database. Future research directions could explore the impact of emerging technologies, such as AR/VR, on personalized shopping experiences and investigate the long-term effects of AI-driven personalization on consumer behavior patterns. This systematic literature review contributes to a deeper understanding of how AI is transforming e-commerce and shaping consumer behavior. The findings underscore the significant potential of AI in enhancing customer engagement, operational efficiency, and brand loyalty, while emphasizing the critical importance of addressing ethical considerations in the rapidly evolving e-commerce landscape.